Unlocking literacy effective decoding & spelling instruction - Henry, Marcia Kierland (Baltimore, Md. P.H. Brookes, 2010)
"Designed for general and special educators of students from prekindergarten to middle school and beyond, Unlocking Literacy offers a wide range of creative strategies for helping students learn and a refresher course on language skills... Filled with engaging classroom activities; lesson plans incorporating multisensory, language-based instruction; samples of student work; explanations of current research; and extensive word lists, this book will help unlock literacy in ways both teachers and students will enjoy."--Book jacket.
Keywords: Reading -- Phonetic method; English language -- Pronunciation -- Study and teaching; English language -- Orthography and spelling -- Study and teaching